Haematopoietic chimerism expressivity in bovine heterosexual twins - KOCHNEVA, M L; GLAZKO, T T; ZHUCHAEV, K V; KOSOVSKIY, G Y; GLAZKO, V I (The Indian Journal of Animal Sciences, 2016)
The aim of the experiment was to study the haematopoietic chimerism in bovine heterosexual twins conceived through artificial insemination and post-embryo transfer. Both animal groups were revealed to have a wide individual range of variability for the expressivity of chimerism that varied from 0 to 96% of cells with the chromosomes of an opposite sex. The study also revealed the tendency towards increased frequency of cytogenetic anomalies in immigrant cells.